Mineralogical, chemical, and petrographic properties of selected South African power stations' feed coals and their corresponding density separated fractions using float-sink and reflux classification methods. Issue 8 (17th November 2019) - Rautenbach, R.; Strydom, C. A.; Bunt, J. R.; Matjie, R. H.; Campbell, Q. P.; Van Alphen, C.
ABSTRACT: Three South African feed coal samples for the combustion process were beneficiated to produce carbon-rich and mineral-rich fractions. The mineralogical, petrographical, and chemical properties of these feed coals and their density separated fractions were investigated using XRD, XRF, QEMSCAN, Electron microprobe, and petrography analyses. This work was conducted with the goal of better understanding the processes and operational problems which could possibly occur during coal utilization, with particular focus on the included and excluded mineral matter transformational behavior at elevated temperatures. The conventional float-sink and reflux classification methods used were shown to successfully eliminate liberated minerals and produced maceral-rich float fractions (98%) macerals. The main differences between the feed coals were related to the mode of occurrence of mineral matter. An integration of these different analytical techniques allowed for better determination of the concentrations of mineral matter responsible for industrial ash-related problems. In this paper, we propose that blends of the different density fractions will reduce or minimize clinker and slag formation as well as the abrasive nature of the clinkers or slags. Possible blends to minimise clinker and slag formation include the float and sink fractions of the feed coals in varying proportions based on the specific mineralogical, petrographical and chemical data.